Research on the construction of agricultural product brand leadership based on consumers' education level - He, Zhihan; Rahman, Khairul Aidil Azlin Abd; Noor, Mohd Sallehuddin Mat (Auricle Global Society of Education and Research, 2023)
Globalization has necessitated the Higher Education Institutions (HEIs) to change the notion of education and leadership policies in the domain of agriculture. The accelerated demand for high quality, large quantity and wide variety of agricultural products, has in turn stimulated the development of global leaders in the agricultural sector by opening the doors for branding the commodities and also for provisioning agricultural education. The distributed educational leadership of China has raised the consumer's educational level, leadership skills, branding of products and patenting innovative products and process. This work investigates the impact of distributed education leadership among the agricultural institutions on the productivity, innovations and education level of consumers in China with the help of data mining and statistical approaches. The empirical analysis is done using Ordinary least squares and Linear Regression to learn whether the variables considered are showing inclined or declined trend in promoting distributed educational leadership. This research will be immensely helpful for entrepreneurs, educationalists and agriculturalists to delegate the responsibility to provincial structures and HEIs which will be beneficial to all the stakeholders of agriculture.